Pengaruh Profitabilitas dan Solvabilitas terhadap Harga Saham Pada Perusahaan Otomotif dan Komponennya yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Talitha Amalia Utami; Liya Megawati (Universitas Batanghari Jambi, 2021)
This research aims to find out, analyze and explain profitability with the Retun On Equity (ROE) proxy, To find out, analyze and explain how Solvency with the Debt to Equity Ratio proxy, To find out, analyze and explain stock prices in automotive companies and their components listed in IDX 2015-2019. To find out, analyze and explain how much influence Profitability with partial Return On Equity (ROE) has on stock prices in automotive companies, to find out, analyze and explain how much influence Solvency with Debt to Equity Ratio (DER) proxy partially on prices shares in automotive companies, to find out how big the simultaneous influence between Profitability with Return On Equty (ROE) and Solvency with Debt to Equity Ratio (DER) proxies on stock prices in automotive companies and their components listed on the IDX in 2015-2019. The type of research used in this study is quantitative research with a descriptive verification approach. The population in this study were 13 companies with a sample of 8 companies in 5 years so that the sample used was 40 samples. By using a non-probability sampling technique, namely using convenience sampling. The data collection technique in this study used literature and documentation studies, namely by collecting panel data needed in this study. Then the data obtained is processed in Eviews 9 Software. The results of the analysis of Profitability (ROE), Solvency (DER) and Stock Price are up and down. Profitability variable (ROE) has no significant and significant effect on stock prices, while the solvency variable (DER) has a significant effect on stock prices. Profitability and solvency variables have no significant effect on stock prices simultaneously. Predictive ability of the two variables on stock prices is 5.78% while the remaining 94% is influenced by other variables that are not in the regression model.